2022
DOI: 10.5194/acp-22-15621-2022
|View full text |Cite
|
Sign up to set email alerts
|

Different physicochemical behaviors of nitrate and ammonium during transport: a case study on Mt. Hua, China

Abstract: Abstract. To understand the chemical evolution of aerosols in the transport process, the chemistry of PM2.5 and nitrogen isotope compositions on the mountainside of Mt. Hua (∼1120 m above sea level, a.s.l.) in inland China during the 2016 summertime were investigated and compared with parallel observations collected at surface sampling site (∼400 m a.s.l.). The PM2.5 exhibited a high level at the mountain foot site (MF; average 76.0±44.1 µg m−3) and could be transported aloft by anabatic valley winds, leading … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 70 publications
0
1
0
Order By: Relevance
“…As indicated in our previous study on Mt. Hua (Wu et al, 2022), insignificant change in the corresponding emission sources was revealed during air mass lifting process. Thus, the daytime samples from both sites were added together as one data matrix.…”
Section: Text S2 Positive Matrix Factorization (Pmf) Source Apportion...supporting
confidence: 57%
“…As indicated in our previous study on Mt. Hua (Wu et al, 2022), insignificant change in the corresponding emission sources was revealed during air mass lifting process. Thus, the daytime samples from both sites were added together as one data matrix.…”
Section: Text S2 Positive Matrix Factorization (Pmf) Source Apportion...supporting
confidence: 57%
“…Gongga through the transboundary transport (Wang, Li et al., 2012a; Wang, Wu, et al., 2012b; Wang et al., 2017; Zong et al., 2018). Then, these air pollutants could be transported aloft by anabatic valley winds (vertical process), leading to the pollutant accumulation on the alpine sampling site because its altitude is generally higher than the boundary layer height (Wu et al., 2022). However, the ambient anhydrosugars in spring and summer could be sourced from the hardwood combustion due to the frequent impact of wildfire emission.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study at Mt. Hua found that changes in sources of primary organic aerosols in the air mass transported from MF to MS were insignificant (Wu et al, 2022) (Figure S3).…”
Section: Enhanced Light Absorption Of Brc In the Mountainous Atmospherementioning
confidence: 93%
“…The horizontal distance between the two sites is ~8 km and the vertical distance is about 1km (Figure S1). More descriptions on the two sites have been documented by our previous study along with the details on the sampling instrument setup (Wu et al, 2022). Hourly concentrations of PM2.5, NO2 and O3 at MS site were monitored by E-BAM (Met One Instruments, USA) and NOx and O3 Analyzer (Thermo, Model 42i, USA; Thermo, Model 49i, USA), respectively.…”
Section: Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation